2011
DOI: 10.1149/1.3633317
|View full text |Cite
|
Sign up to set email alerts
|

Different Properties of Erbium Silicides on Si(100) and Si(551) Orientation Surfaces

Abstract: The electrical and physical properties of ErSi x on n-type Si(100) and Si(551) surfaces are reported. The Schottky barrier heights (SBHs) depend on the Si substrate orientation. On a Si(100) surface, a low electron SBH around 0.3 eV is obtained and the obtained SBH is larger than 0.4 eV on a Si(551) surface, while this difference is caused by the quantity of Si atoms in ErSi x and on Si(100) this is less than on Si(551). These silicidation reactions are very important to develop the future high current drivabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…It is considered that the work function difference is caused by the film stress on ErSi x . We have already reported the quantity of Si atoms in ErSi x and the SBH are changed between Si(100) and Si(551) (17). More Si contains in ErSi x on Si(551) surface compared with that on Si(100).…”
Section: Resultsmentioning
confidence: 97%
“…It is considered that the work function difference is caused by the film stress on ErSi x . We have already reported the quantity of Si atoms in ErSi x and the SBH are changed between Si(100) and Si(551) (17). More Si contains in ErSi x on Si(551) surface compared with that on Si(100).…”
Section: Resultsmentioning
confidence: 97%
“…In Si(111) case, the SBHs are independent of Er deposition thickness and very low SBHs as around 0.25 eV are observed. On Si(551), ErSi x (0001) tends to grow on Si(111) has been reported (17). It is considered that the SBH is not determined by the growth of the ErSi x crystal orientation, but is determined by the silicon surface orientations Fig.…”
Section: Resultsmentioning
confidence: 98%
“…We have already reported that the contact resistance on any crystal orientation p + -silicon can be reduced by using Pd 2 Si (11). However, we have also reported the properties of ErSi x on Si(100), ( 111) and ( 551) surfaces (17,18) and a reducing SBH on Si(551) surface is more difficult than that on Si(100). In this paper, we investigated SBH diode properties of ErSix and influences of the ErSix crystallinity on n-type Si(100) and Si(551) surfaces.…”
Section: Introductionmentioning
confidence: 85%
“…The low R c due to low SBH is obtained using erbium silicide (ErSi x ) for n + silicon and palladium silicide (Pd 2 Si) for p + silicon on Si(100) (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%